Cinema 4D Essential Training: 9 Particles and Dynamics. - Garrott, Rob (linkedin.com, 2012)
Introduces particles (used to simulate effects like snow, sparks, fog, or fire) and dynamics (which allow you to define how objects interact with their environment).